The identity of Anemone weixiensis (Ranunculaceae) from northwestern Yunnan, China - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2019)
Examination of herbarium specimens (including type material) has shown that Anemone weixiensis, recently described from Weixi County in northwestern Yunnan, China, is conspecific with A. flaccida, a species widely distributed in China, Japan and Russia (Far East) and fairly common in northwestern Yunnan. We therefore place A. weixiensis in synonymy with A. flaccida. As A. flaccida belongs to A. sect. Keiskea based on molecular work, we reduce A. sect. Deinostigma, which was established to accommodate A. weixiensis, to the synonymy of A. sect. Keiskea.